The Influence of Top Results, Number of Labor and Within Time on Tea Production Volume at PT Pagilaran UP Pagilaran Batang - Shifa Nur Syidah; Rara Ririn Budi Utaminingtyas; Isnaini - Nurkhayati (Politeknik Negeri Semarang, 2021)
Tea is one of the result in Indonesian agricultural and plantation commodities. Today the tea is produced into powdered tea. There are some production factors affect the volume of tea production. This research aims to know the influence of tea leaves yield, amount of labors, and withering time of tea leaves as independent variables to the volume of tea production as the dependent variable at PT Pagilaran, Pagilaran Production Unit. This research used secondary data in the numbers form and then analyzed by classical assumption test, multiple linear regression analysis, and goodness of fit model. The results showed that tea leaves yield and withering time of tea leaves have significant influence on the volume of tea production, while the amount of labors have not significantly influence on the volume of tea production. Furthermore, tea leaves yield, amount of labors, and withering time of tea leaves together influence the volume of tea production at PT Pagilaran, Pagilaran Production Unit. Based on this research, it's also known that the most dominant factor influencing the volume of tea production at PT Pagilaran, Pagilaran Production Unit is tea leaves yield.